2020
DOI: 10.1186/s12941-020-0345-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of plasma lopinavir and ritonavir in tuberculosis–HIV co-infected African adult patients also receiving rifabutin 150 or 300 mg three times per week

Abstract: Background: To evaluate the pharmacokinetic of plasma lopinavir (LPV) and ritonavir (RTV) when co-administered with three times weekly (TPW) rifabutin (RBT) at a dose of either 150 or 300 mg in African tuberculosis (TB) and HIV co-infected adult patients. Methods: This is a pharmacokinetic study conducted in Ouagadougou among patients treated with a standard dosage of LPV/RTV 400/100 mg twice daily and RBT 150 mg TPW (arm A = 9 patients) or rifabutin 300 mg TPW (arm B = 7 patients) based regimens. Patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Under such conditions, lopinavir reaches about 10 µg/mL (15.9 µM) after an 800 mg dose. For its part, ritonavir has a bioavailability of 85%, and C max of about 11 µg/mL (15.5 µM) are observed after administration of a 600 mg oral dose 29 . Importantly, because of strong CYP3A4 inhibition, major drug‐drug interactions are observed with other CYP3A4 substrates 30–32 …”
Section: Resultsmentioning
confidence: 99%
“…Under such conditions, lopinavir reaches about 10 µg/mL (15.9 µM) after an 800 mg dose. For its part, ritonavir has a bioavailability of 85%, and C max of about 11 µg/mL (15.5 µM) are observed after administration of a 600 mg oral dose 29 . Importantly, because of strong CYP3A4 inhibition, major drug‐drug interactions are observed with other CYP3A4 substrates 30–32 …”
Section: Resultsmentioning
confidence: 99%
“…For its part, ritonavir has a bioavailability of 85%, and C max of about 11 μg/mL (15.5 μM) are observed after administration of a 600 mg oral dose. 29 Importantly, because of strong CYP3A4 inhibition, major drug-drug interactions are observed with other CYP3A4 substrates. 30-32…”
Section: Resultsmentioning
confidence: 99%
“…However, co‐administration with ritonavir (RTV; an inhibitor of the cytochromeP450 3A isoenzyme) inhibits LPV metabolism, significantly increasing plasma concentrations of the drug and affording high and consistent levels of LPV. Thus, a co‐formulation of LPV and RTV (LPV/RTV) has been developed for clinical use 15,16 . For instance, Cao et al conducted a randomized, controlled, open‐label trial involving hospitalized adult patients with confirmed SARS‐CoV‐2 infection.…”
Section: Lopinavir and Ritonavirmentioning
confidence: 99%